2007
DOI: 10.1002/ajmg.a.31613
|View full text |Cite
|
Sign up to set email alerts
|

Congenital arhinia: Molecular‐genetic analysis of five patients

Abstract: Congenital arhinia, complete absence of the nose, is an extremely rare anomaly with unknown cause. To our knowledge, a total of 36 cases have been reported, but there has been no molecular-genetic study on this anomaly. We encountered a sporadic case of congenital arhinia associated with a de novo chromosomal translocation, t(3;12)(q13.2;p11.2). This led us to analyze the patient by BAC-based FISH for translocation breakpoints and whole-genome array CGH for other possible deletions/duplications in the genome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…For instance, the SIX3 gene found on HSA2p21, and linked to the posterior condylion measure in baboons, has been identified as a causative factor in holoprosencephaly, a disorder with severe craniofacial dysmorphology including cyclopia and a midline proboscis situated above the eye (Wallis et al 1999). Sato et al (2007) identified a patient with a deletion spanning HSA3q11.2, linked to the trait GoGn-S in our study, that presented with the rare condition of congenital arhinia (complete absence of the nose). Additionally, deletions in the HSA17p12 region, linked to N-Pr in this study, have been implicated in cleft palate associated with Smith-Magenis syndrome (Andrieux et al 2007).…”
Section: Discussionmentioning
confidence: 51%
“…For instance, the SIX3 gene found on HSA2p21, and linked to the posterior condylion measure in baboons, has been identified as a causative factor in holoprosencephaly, a disorder with severe craniofacial dysmorphology including cyclopia and a midline proboscis situated above the eye (Wallis et al 1999). Sato et al (2007) identified a patient with a deletion spanning HSA3q11.2, linked to the trait GoGn-S in our study, that presented with the rare condition of congenital arhinia (complete absence of the nose). Additionally, deletions in the HSA17p12 region, linked to N-Pr in this study, have been implicated in cleft palate associated with Smith-Magenis syndrome (Andrieux et al 2007).…”
Section: Discussionmentioning
confidence: 51%
“…The chromosomal analysis in patients with arhinia showed normal results, excepting for 3 cases that had an abnormal karyotype: mos46, XX/47, XX, +9 [7]; 46, XY, inv(9) [8]; 46, XX, t(3;12) (q13.2; p11.2) (de novo) [9]. The third patient was also discovered to be the carrier of a 19 Mb deletion spanning from 3q11.2 to 3q13.31 at the 3q breakpoint of the translocation [10]. As the deleted segment at 3q was a strong candidate region for a putative arhinia gene, array CGH was performed in other arhinia patients, as well as mutation analysis of candidate genes [10].…”
Section: Discussionmentioning
confidence: 94%
“…The third patient was also discovered to be the carrier of a 19 Mb deletion spanning from 3q11.2 to 3q13.31 at the 3q breakpoint of the translocation [10]. As the deleted segment at 3q was a strong candidate region for a putative arhinia gene, array CGH was performed in other arhinia patients, as well as mutation analysis of candidate genes [10]. No consistent gene mutations have been discovered so far; therefore, genetic testing for a putative arhinia gene is not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is unclear as to whether BAMS is genetically heterogeneous. This lack of information makes it difficult to establish an estimated frequency for BAMS, but 14 patients have been described in the literature (Table 1), making this the 15th reported case and the first reported case in a Mexican patient (Bosma et al, 1981;Thiele et al, 1996;Graham and Lee, 2006;Akkuzu et al, 2007;Sato et al, 2007;Tryggestad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There have been only 37 reported cases of arrhinia (Olsen et al, 2001;Sato et al, 2007;Goyal et al, 2008). The spectrum of clinical manifestations with arrhinia includes midline defects and involves palatal, ocular, facial, and ear abnormalities.…”
Section: Discussionmentioning
confidence: 99%